Non-bullous Impetigo: Incidence, Prevalence, and Treatment in the Pediatric Primary Care Setting in Italy - Barbieri, Elisa; Porcu, Gloria; Dona', Daniele; Falsetto, Nathalie; Biava, Mirella; Scamarcia, Antonio; Cantarutti, Luigi; Cantarutti, Anna; Giaquinto, Carlo (Frontiers in Pediatrics, 2022)
Impetigo is a common skin infection in children. The worldwide prevalence in children is estimated to be 11%, however, because of scarce and outdated studies, the burden of impetigo in high-income countries is overestimated. This research aims to evaluate the incidence and management of children with non-bullous impetigo (NBI) residing in Italy. This retrospective cohort study included children up to 14 years of age enrolled in the Pedianet database from January 2004 to June 2018. Events were identified by searching ICD9-CM codes (684 and 694.3) and free text fields for a diagnosis of NBI reported during a primary care visit. Diagnoses were manually validated, and events registered within 30-days after the index date were considered follow-ups. Incidence (IR) rates of NBI were stratified by sex, age group, and calendar year. Topical and systemic antibiotic treatments were grouped based on ATC codes. 15,136 NBI episodes occurred in a total cohort of 225,979 children. The overall IR of NBI was 9.5 per 1000 person-years, and children aged 1-4 years had the highest IR (13.2 per 1000 person-years). A significant decrease in NBI IR from 13 per 1000 person-years in 2004 to 7.5 per 1000 person-years in 2018 (p<0.0001) was noted. Most of the episodes were treated; systemic antibiotics were preferred over topical. The prevalence of NBI in children in Italy is less than one-third than the global estimate and the trend in time is decreasing. Over prescriptions of systemic antibiotics, not in line with guidelines, pose a threat to the diffusion of antimicrobial resistance.